Equation 1) 4x = 3y - 2
Equation 2) 18 = 3x + y
Turn both equations into ax + by = c form.
Subtract 3y from both sides on equation 1, as well as subtracting 3x from both sides on the 2nd equation. Then, subtract 18 from both sides, and then subtract y from both sides, on the 2nd equation.
1) 4x - 3y= -2
2) -3x - y = -18
Multiply ALL of equation 2 by 3.
2) 3(-3x - y = -18)
Simplify.
2) -9x - 3y = -54
1) 4x - 3y = -2
Subtract equations from one another.
-13x = -52
Divide both sides by -13/
x = 4
Plug in 4 for x in the first equation.
4x - 3y = -2
4(4) - 3y = -2
Simplify.
16 - 3y = -2
Subtract 16 from both sides.
-3y = -18
Divide both sides by -3.
y = 6
So, x = 4, y = 6
A : (4, 6)
~Hope I helped!~